Neuroanatomy of a hydrothermal vent shrimp provides insights into the evolution of crustacean integrative brain centers - Julia Machon; Jakob Krieger; Rebecca Meth; Magali Zbinden; Juliette Ravaux; Nicolas Montagné; Thomas Chertemps; Steffen Harzsch (eLife, 2019)
Alvinocaridid shrimps are emblematic representatives of the deep hydrothermal vent fauna at the Mid-Atlantic Ridge. They are adapted to a mostly aphotic habitat with extreme physicochemical conditions in the vicinity of the hydrothermal fluid emissions. Here, we investigated the brain architecture of the vent shrimp Rimicaris exoculata to understand possible adaptations of its nervous system to the hydrothermal sensory landscape. Its brain is modified from the crustacean brain ground pattern by featuring relatively small visual and olfactory neuropils that contrast with well-developed higher integrative centers, the hemiellipsoid bodies. We propose that these structures in vent shrimps may fulfill functions in addition to higher order sensory processing and suggest a role in place memory. Our study promotes vent shrimps as fascinating models to gain insights into sensory adaptations to peculiar environmental conditions, and the evolutionary transformation of specific brain areas in Crustacea.